A new species of Fissarcturus Brandt, 1990 (Isopoda, Valvifera, Antarcturidae) from the Southern Ocean, off the South Sandwich Islands - Nickel, Judith M.; Brandt, Angelika (Zootaxa, 2013)
A new antarcturid species, Fissarcturus dorotheae sp. nov., from the Southern Ocean is described. During the ANDEEP II expedition in March 2002, specimens of the new species were collected aboard the RV Polarstern off the South Sandwich Islands. The new species is most similar to Fissarcturus sandwichi Brandt, 2007, but can be easily distinguished from it by the absence of the cauliflower-like spination, the number of articles of the antennal flagellum as well as the coxal spination. It also can be differentiated from F. sandwichi by the spinulation of the supraocular spines, the tubercular-like spination of the cephalothorax and the absence of tubercles and denticulate spines on the pereopods. The new species differs from all other species of the genus by the strong spinulated frontally bent supraocular spines and the weakly pronounced dorsal spination. A distribution map of all known Fissarcturus species is provided.